Pengembangan Media Pembelajaran Interaktif Menggunakan Powerpoint Berbasis Animasi Pada Materi Sel Di Kelas XI SMAN 8 Medan - ., Ismy Aisyah Lubis; ., Khairuddin; ., Rasyidah (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This study aims to determine how to develop interactive learning media using powerpoint-based animation in cell biology lessons and determine the feasibility of the media developed based on the results of validation by the validator. This study uses the ADDIE model of research and development (R&D) (Analysis, Design, Development, Implementation, and Evaluation). The sample in this study were students of class XI MIPA 1, 2 and 4 SMAN8 Medan. The trial was carried out in small groups to 15 students and large group trials to 50 students through a response questionnaire sheet. Based on the results of media expert validation, the overall aspect obtained an average score of 86.2% with a very decent category. The results of material expert validation obtained an average score of 75% with a decent category. The results of the validation of linguists obtained an average score of 93.6% with a very decent category. The results of the teacher's assessment response obtained an average score of 90.625% with a very decent category. The results of the student assessment responses in the small group trial obtained an average score of 94% and in the large group trial an average score of 87% was obtained in the very feasible category.